Postoperative testicular abscess with bacteremia due to Actinomyces neuii - Juan Carlos Rico Crescencio (IDCases, 2014)
Bacteremia due to Actinomyces neuii has been reported in the literature 14 times. A. neuii is an endogenous organism that has been cultured in clinical specimens of the genitourinary tract; we are reporting a unique case of A. neuii postoperative testicular abscess with bacteremia which was successfully treated with surgery and a short course of parenteral antimicrobials.